2010
DOI: 10.1104/pp.109.151027
|View full text |Cite
|
Sign up to set email alerts
|

PlantMetabolomics.org: A Web Portal for Plant Metabolomics Experiments

Abstract: PlantMetabolomics.org (PM) is a web portal and database for exploring, visualizing, and downloading plant metabolomics data. Widespread public access to well-annotated metabolomics datasets is essential for establishing metabolomics as a functional genomics tool. PM integrates metabolomics data generated from different analytical platforms from multiple laboratories along with the key visualization tools such as ratio and error plots. Visualization tools can quickly show how one condition compares to another a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 25 publications
0
72
0
Order By: Relevance
“…Our recommendations include methods for sampling, extraction and storage, metabolite identification, processing of large sample numbers, and recommendations for reporting the methods of metabolite identification and the levels of certainty in metabolite quantification. Good suggestions for standards in reporting chemical ontology and supporting metadata have already been made by Sumner et al (2007) and Bais et al (2010).…”
mentioning
confidence: 99%
“…Our recommendations include methods for sampling, extraction and storage, metabolite identification, processing of large sample numbers, and recommendations for reporting the methods of metabolite identification and the levels of certainty in metabolite quantification. Good suggestions for standards in reporting chemical ontology and supporting metadata have already been made by Sumner et al (2007) and Bais et al (2010).…”
mentioning
confidence: 99%
“…Based on a comparison of our data set and the PlantMetabolomics.org data set (Bais et al, 2010, we report at least partial mutual data complementarity (comparing only GC-MS metabolomics; Fig. 3A).…”
Section: Discussionmentioning
confidence: 99%
“…When we compared the mutants on our list (Supplemental Table S1) with those generated by the Arabidopsis 2010 Plant Metabolomics Consortium (Bais et al, 2010Quanbeck et al, 2012;Hur et al, 2013; http://www.metnetdb.org/pmr/), we found that on both, pad4-1 (Arabidopsis Biological Resource Center identifier CS3806; AT3G52430, encoding the ARABIDOPSIS PHYTOALEXIN DEFICIENT4 [PAD4] a/b-hydrolase superfamily protein; Fig. 3A) was analyzed by GC-MS.…”
Section: Systematic Data Comparison Demonstrates That Meko Complementmentioning
confidence: 99%
See 2 more Smart Citations